. - Jofré, Manuel (Revista Chilena de Literatura, 2005)
Some of Mijail Bachtin's theses are discussed here. First the opposition between the dialogic novel and the polyphonic; in the second place, the pertinence of Socratic dialogue and the Menippean satire in the fictional structure itself; thirdly, the pertinence of monologism in the approach to a historical poetic; and lastly, some of the aspects of carnavalization in the novel.